The effects of financial literacy and materialism on the savings decision of generation Z Indonesians - Stevanus Pangestu (Taylor & Francis Group, 2020)
The purpose of this research is to analyze the influence of financial literacy and materialism on the savings decision of Indonesia’s generation Z. This study was motivated by the country’s agenda to achieve financial inclusion and develop human resources throughout the nation. We distributed questionnaires to 430 university students to measure their financial literacy score and materialism level, as well as the savings rate of every respondent. Through a series of regression analyses, we find that (i) age, gender, and major of study significantly influence financial literacy score; (ii) financial literacy positively influences savings decision; and (iii) materialism negatively influences savings decision. Our findings generally foretell favourable financial conditions for future generations of Indonesians. Finally, we also strongly recommend policymakers to start integrating financial education as a compulsory part of every school’s curriculum, regardless of level.